2017
DOI: 10.5194/hess-21-6167-2017
|View full text |Cite
|
Sign up to set email alerts
|

Conserving the Ogallala Aquifer in southwestern Kansas: from the wells to people, a holistic coupled natural–human model

Abstract: Abstract. The impact of water policy on conserving the Ogallala Aquifer in Groundwater Management District 3 (GMD3) in southwestern Kansas is analyzed using a system-level theoretical approach integrating agricultural water and land use patterns, changing climate, economic trends, and population dynamics. In so doing, we (1) model the current hyper-extractive coupled natural-human (CNH) system, (2) forecast outcomes of policy scenarios transitioning the current groundwater-based economic system toward more sus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, several studies have been able to address this issue by applying PMP iteratively in combination with separate crop growth and hydrological models. Aistrup et al [21] applied the formulation to Groundwater Management District 3 (GMD3) in southwestern Kansas in which PMP is used with a plant growth model integrating water and land use patterns, changing climate, economic trends, and population dynamics. In California, MacEwan et al [22] developed a modular hydroeconomic modeling approach integrating California's C2VSim groundwater-surface water simulation model with the Statewide Agricultural Production (SWAP) economic model.…”
Section: Mrvaa Water Table Elevationmentioning
confidence: 99%
“…However, several studies have been able to address this issue by applying PMP iteratively in combination with separate crop growth and hydrological models. Aistrup et al [21] applied the formulation to Groundwater Management District 3 (GMD3) in southwestern Kansas in which PMP is used with a plant growth model integrating water and land use patterns, changing climate, economic trends, and population dynamics. In California, MacEwan et al [22] developed a modular hydroeconomic modeling approach integrating California's C2VSim groundwater-surface water simulation model with the Statewide Agricultural Production (SWAP) economic model.…”
Section: Mrvaa Water Table Elevationmentioning
confidence: 99%
“…For example, 20 to 25% additional land can be irrigated using center-pivot sprinklers in comparison with gravity-based furrow irrigation [32]. Aistrup et al [14] and Upendram and Peterson [35] discussed the increase of irrigated area in the HPA region resulting from surplus water availability due to water conservation practices, and found that climatic and economic factors (droughts, net returns on irrigated land) mainly govern the expansion.…”
Section: Irrigation Application Efficiencymentioning
confidence: 99%
“…Over-drafting is the most crucial issue challenging the sustainability of the HPA [14]. Alley et al [15] described the sustainability of the groundwater resources as a well-planned utilization and development of the aquifer, ensuring the indefinite or long-term availability of water.…”
Section: Introductionmentioning
confidence: 99%